PENGARUH PEMBERIAN KOMPENSASI DAN MOTIVASI KERJ A TERHADAP LOYALITAS KARYAWAN DAN DAMPAKNYA PADA KINERJA KARYAWAN (Studi pada CV AL-ACHWAN) - Al Tarom, Ilham Rizki; Yuniawan, Ahyar (Diponegoro Journal of Management, 2019)
Human resources play a very important role in a company because humans are thedeterminant of the running of the company. One of the company's successes is measuredthrough employee performance. The higher the employee's performance, the higher thesuccess achieved by the company. The purpose of this study was to analyze the effect ofcompensation and work motivation on employee loyalty and its impact on employeeperformance.The population in this study were employees of CV Al-Achwan. This research wasconducted by distributing questionnaires with a sample of 130 employees using simplerandom sampling method. The data analysis method used is multiple regression analysis.The data testing techniques used in this study include path analysis test, and sobel test totest the mediation effect.The results showed that giving compensation has a positive effect on employeeloyalty, work motivation has a positive effect on employee loyalty, compensation has apositive effect on employee performance, work motivation has a positive effect onemployee performance, employee loyalty has a positive and significant effect on employeeperformance.